Non-Interference Principle Dynamics in ASEAN and African Union Responses to Member States’ Unconstitutional Changes of Government - Ulandari, Ulandari; Gautama, Budi Arundhati; Indrayati, Rosita (Fakultas Hukum Universitas Islam Jakarta, 2025)
Unconstitutional changes of government (UCG) are a serious challenge to regional stability and the principles of international law, especially the principle of non-interference. The African Union (AU) and the Association of Southeast Asian Nations (ASEAN) are facing different dynamics in responding to the phenomenon. This study aims to analyze the influence of the United Nations' attitude on the application of the principle of non-interference and analyze the response of ASEAN and AU to the UCG in their member countries. The research uses normative juridical methods with legislative, case, and comparative approaches. The results of the study show that the AU has adapted the principle of non-interference through the Constitutive Act of The African Union by including an exception clause, including in situations of grave circumstances (war crimes, genocide, and crimes against humanity) or at the request of the country concerned. Meanwhile, ASEAN still maintains the strict application of the principle of non-interference without a specific legal mechanism to respond to the UCG, as happened in Myanmar. It can be concluded that the dynamics of the application of the principle of non-interference show a shift in norms and a transformation of legal approaches at the regional level, where the AU has moved towards adapting new norms, while ASEAN is still prioritizing the path of diplomacy and political consensus. As a recommendation, ASEAN needs to strengthen the legal legitimacy of the 'Five-Point Consensus' as a model for handling the UCG in the region, so that it can function as a constitutional instrument that supports stability and sustainable regional legal governance.